Multifunctional operation of current controlled VSI based on the harmonic content of PCC voltage - Bonaldo, Jakson Paulo; Schiavon, Gilson; Paredes, Helmo K. Morales [UNESP]; Pomilio, José Antenor (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper proposes a technique to perform the multifunctional use of current controlled voltage source inverters used primarily as interface between renewable energy sources and the grid utility. The strategy adopted doesn't demand sensing the grid current neither the load current. Instead, the reference signal for compensation purpose is obtained by filtering the harmonics components of the voltage in the coupling point of the multifunctional inverter. Then, the extracted harmonics are multiplied by a dynamic factor for amplitude adjustment resulting in the reference current for compensation. The reference for active power injection is added to the compensation reference creating the current reference for the inverter. The operation of the proposed strategy is demonstrated through simulation and experimental results and its main advantages and limitations are indicated and discussed along the work.
Keywords: Current controlled voltage source inverters; Microgrids; Multifunctional inverters; Power Quality